Ketogenic Diets Induced Glucose Intolerance and Lipid Accumulation in Mice with Alterations in Gut Microbiota and Metabolites - Li, Yue; Yang, Xin; Zhang, Jing; Jiang, Tianyi; Zhang, Ziyi; Wang, Zhiyi; Gong, Mengxue; Zhao, Liping; Zhang, Chenhong (mBio, 2021)
The ketogenic diet with extremely high fat and very low carbohydrate levels is very popular in society today. Although it has beneficial effects on epilepsy and neurodegenerative diseases, how ketogenic diets impact host glucose and lipid metabolism and gut microbiota still needs further investigation. The ketogenic diet (KD), which can induce changes in gut microbiota, has shown benefits for epilepsy and several neurodegenerative diseases. However, the effects of a KD on glucose and lipid metabolism remain inconclusive. Using two formulas of ketogenic diets (KDR with 89.5% fat and KDH with 91.3% fat), which are commonly used in mouse trials, we found that KDR but not KDH induced insulin resistance and damaged glucose homeostasis, while KDH induced more fat accumulation in mice. Further study showed that KD impacted glucose metabolism, which was related to the sources of fat, while both the sources and proportions of fat affected lipid metabolism. And the KD widely used in human studies still induced insulin resistance and fat accumulation in mice. Moreover, KDs changed the gut microbiota and metabolites in mice, and the sources and proportions of fat in the diets respectively changed the abundance of specific bacteria and metabolites which were correlated with parameters related to glucose intolerance and lipid accumulation. Overall, our study demonstrated that the metabolic disorders induced by KDs are closely related to the source and proportion of fat in the diet, which may be associated with the changes of the gut microbiota and metabolites. IMPORTANCE The ketogenic diet with extremely high fat and very low carbohydrate levels is very popular in society today. Although it has beneficial effects on epilepsy and neurodegenerative diseases, how ketogenic diets impact host glucose and lipid metabolism and gut microbiota still needs further investigation. Here, we surveyed the effects of two ketogenic diets which are commonly used in mouse trials on metabolic phenotypes, gut microbiota, and metabolites in mice. We found that both ketogenic diets impaired glucose and lipid metabolism in mice, and this may be due to the sources and proportions of fat in the diets. This work highlights the potential risk of glucose and lipid metabolism disorders and the importance of evaluating the sources and proportions of fat in the diets, when using ketogenic diets for weight loss and the treatment of diseases.